Incidence of Communicable and Non-Communicable Disease for Small Island Communities/Developing States: A Systematic Review and Proportional Meta-Analysis - Simanjuntak, Arya Marganda; Ruthcinthamy, Stevany Risdewanty; Girsang, Agnes Ivana; Suyanto; Yusdiana (SCRIPTA SCORE Scientific Medical Journal, 2025)
Background: Small Island Communities (SIDS) are remote, vulnerable areas with unique challenges like weather changes, limited healthcare access, and limited epidemiological data. Studies on diseases like obesity and depression are limited, and a systematic review is needed to assess current incidence and risk in these communities. Methods: A Systematic review was conducting using search engines. Keywords utilized such as: “Small Island Community [MeSH] OR Small Island Developing States [MeSH]” AND “Incidence OR Prevalence OR Disease”. Each author conducted an independent analysis of each paper based on its title, abstract, and applicability for the PEOS framework. JBI critical appraisal techniques were used to assess the risk of bias in all included research. Results: 18 publications from different nations, such as Indonesia, Jamaica, Solomon Island, and others, were included in the 404.795 articles. All writers then synthesized the articles, which were then examined using JBI. The prevalence of communicable disease infected 99% of community including worm infections, conjunctivitis, malaria, and COVID-19 is particularly high in small island settings in nations like Indonesia, Jamaica, Vanuatu, the Solomon Islands, and Fiji. Risk is enhanced by factors including socioeconomic status and educational attainment. Analysis for non-communicable illnesses affected 27% of community include lung cancer, stress, obesity, stunting, depression, and hypertension. JBI score for all included is 75%, considered moderate risk of bias. Conclusions: Small Island communities face diverse diseases, requiring research and tailored solutions due to economic, environmental, and socio-cultural factors. Keyword: Communicable Disease, Meta-Analysis, Non-Communicable Disease, Small Island Community Latar Belakang: Komunitas Pulau Kecil adalah daerah terpencil dan rentan dengan tantangan yang unik seperti perubahan cuaca, akses layanan kesehatan yang terbatas, dan kurangnya penelitian. Penelitian tentang penyakit seperti obesitas dan depresi masih terbatas, dan tinjauan sistematis diperlukan untuk menilai kejadian dan risiko saat ini di komunitas ini. Tujuan: Menentukan kejadian atau risiko penyakit menular atau tidak menular untuk masyarakat pulau kecil/negara berkembang. Metode: Tinjauan sistematis menggunakan berbagai mesin pencari. Kata kunci yang digunakan seperti: “Komunitas Pulau Kecil [MeSH] ATAU Negara Berkembang Pulau Kecil [MeSH]” DAN “Insiden ATAU Prevalensi ATAU Penyakit”. Semua artikel dianalisis secara independen oleh semua penulis berdasarkan judul, abstrak dan kesesuaian dengan kerangka kerja PEOS. Semua studi yang disertakan dianalisis untuk risiko bias menggunakan alat penilaian kritis Joanna-Briggs Institute (JBI). Hasil: Sebanyak 18 publikasi dari berbagai negara, seperti Indonesia, Jamaika, Solomon Island, dan lainnya, termasuk dalam 404.795 artikel tersebut. Semua penulis kemudian mensintesis artikel-artikel tersebut, yang kemudian diperiksa menggunakan JBI. Prevalensi penyakit menular yang menjangkiti 99% masyarakat termasuk infeksi cacing, konjungtivitis, malaria, dan COVID-19 sangat tinggi di negara-negara kepulauan kecil seperti Indonesia, Jamaika, Vanuatu, Kepulauan Solomon, dan Fiji. Risiko ini diperkuat oleh faktor-faktor termasuk status sosial ekonomi dan tingkat pendidikan. Analisis untuk penyakit tidak menular yang mempengaruhi 27% masyarakat termasuk kanker paru-paru, stres, obesitas, stunting, depresi, dan hipertensi. Skor JBI untuk semua yang termasuk adalah 75%, dianggap sebagai risiko bias sedang. Kesimpulan: Masyarakat pulau kecil menghadapi beragam penyakit, yang membutuhkan penelitian dan solusi yang disesuaikan dengan faktor ekonomi, lingkungan, dan sosial-budaya. Kata Kunci: Masyarakat Pulau Kecil, Meta Analisis, Penyakit Menular, Penyakit Tidak Menular